Defending qualitative research : design, analysis and textualization - Cardano, Mario (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Focusing on the phases of qualitative research which precede and follow fieldwork - design, analysis, and textualization - this book offers new theoretical tools to tackle one of the most common criticisms advanced against qualitative research: its presumed lack of rigour. Rejecting the notion of 'rigour' as formulated in quantitative research and based on the theory of probability, it proposes a theoretical frame that allows combining the goals of rigour and that of creativity through the reference to theory of argumentation. As such, it will appeal to scholars and students across the social sciences with interests in qualitative research methods"--
OCLC-licensed vendor bibliographic record.
Keywords: Research -- Methodology; Qualitative research; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General